Strategi Organisasi Perempuan Anti Trafficking Apne Aap dalam Penanggulangan Isu Perdagangan Manusia Di India - CICI ANISA FIRMALIZA (Department of International Relations, Universitas Andalas)
This research attempts to analyze strategy and effort undertaken by an anti-trafficking NGO called Apne Aap on addressing human trafficking issue in India. The most crucial thing in this analyzing is to figure out the meaning contained behind those strategy and effort. This research puts three main concepts; strategy of Korten NGO generation, human trafficking, and women interests. The observed knowledge is produced by applying feminist methodology. The finding of this research shows that the strategies of Apne Aap tend to address the problem in society particularly the beneficiaries Apne Aap. The meaning found is the fundamental change ideologically for women group in India. It is not merely on how the number of human trafficking decline, moreover the verily fundamental change is on how woman can maximize whole potential on herself thus it can generate high independency and self-confidence to express her group and personal interests. This will also allow them to be free from any oppression and discrimination, including human trafficking.